FAMILY OF MAULANA NOORANI: خانوادہ مولانا نورانی :احوال وآثا ر - Bhati, Haris (International Research Journal of Arabic and Islamic Studies, 2021)
Allama Maulana Shah Ahmed Noorani belongs to one of the respectable educated family of sub-continent Indo-Pak. His family has been involved lineally in religious guidance of Muslims and kept involved in amelioration of Muslim Ummah. Even before establishment of Pakistan his ancestors has been serving different countries in academic, literature, political and social sectors. For the creation of Pakistan his father Maulana Abdul Aleem Siddiqui, his uncle Maulana Nazeer Ahmed Khajandi and he himself participated with heart and soul. His father Moulana Abdul Aleem Siddiqui has come across several homiletic visits in number of countries and keep informed about the malicious conspiracies of skeptic Qadyanis and completely rejected Qadyani deism at every platform. After the death of his beloved father he has extended mission of homiletic preaching of religion (Islam).